2012
DOI: 10.1097/mnh.0b013e32834de4ee
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D

Abstract: Purpose of review Great progress has been made in recent years in understanding the expanding roles of the vitamin D endocrine system beyond calcemic regulation, including pathophysiological actions in the kidney and the cardiovascular system. The purpose of this review is to update the recent advance regarding the effects of vitamin D and its analogs on the renal and cardiovascular system. Recent findings Vitamin D-deficiency is not only widely associated with chronic kidney disease and cardiovascular disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 88 publications
1
22
0
Order By: Relevance
“…Stimulation of vitamin D receptors exerts protective activity through multiple mechanisms, including inhibition of the RAS, regulation of proliferation and differentiation, reduction of proteinuria, anti-inflammation, and anti-fibrosis [103] . Growing evidence indicates that vitamin D exerts anti-proteinuric and renoprotective effects in DKD patients.…”
Section: Vitamin D Receptor Activationmentioning
confidence: 99%
“…Stimulation of vitamin D receptors exerts protective activity through multiple mechanisms, including inhibition of the RAS, regulation of proliferation and differentiation, reduction of proteinuria, anti-inflammation, and anti-fibrosis [103] . Growing evidence indicates that vitamin D exerts anti-proteinuric and renoprotective effects in DKD patients.…”
Section: Vitamin D Receptor Activationmentioning
confidence: 99%
“…As a predictor of CVD, hyperuricemia has been long observed to occur with an increased frequency among population with high risks for CVD [2], [3]. Moreover, some previous studies found that vitamin D deficiency was an independent risk factor for CVD [4] and a predictor of chronic kidney diseases [5]. Impaired renal function was suggested to raise serum uric acid (SUA) concentration by decreasing renal excretion [6].…”
Section: Introductionmentioning
confidence: 99%
“…25(OH)D mediates its effects via ligand-regulated vitamin D receptors [24] expressed in target organs directly involved in calcium homeostasis (bones, kidneys, intestinal tract, and the parathyroid gland), as well as other target organs including skeletal muscles, smooth muscle cells, and myocardium [25]. Through selective activation of vitamin D receptors, 25(OH)D exerts hormonal, autocrine and paracrine actions [26] that are increasingly recognized as essential to maintaining cardiovascular health [27].…”
Section: Discussionmentioning
confidence: 99%